PV STATCOM BASED CONTROL STRATEGIES FOR POWER QUALITY ENHANCEMENT - Somasundaram, PL. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
Due to increasing demands in electric power it becomes more significant to usethe available energy sources efficiently. Renewable energy sources like wind, sun, and hydro are seen as a dependable alternative to the traditional energy sources such as oil, natural gas, or coal. In the current work, a novel concept of utilizing a photovoltaic solar farm inverter as STATCOM, called PV-STATCOM, for improving stable power transfer limits of the interconnected transmission system. The complete inverter rating of the PV solar farm, which remains dormant during nighttime, during daytime the inverter capacity absent after real power production is used to accomplish the aforementioned goal. The validation of the proposed operation is done through MATLAB simulation.